Recruitment and Retention at the Grass Roots - McLennan, B.; Dunlop, Patrick (2019)
Drs Blythe McLennan and Patrick Dunlop will discuss the challenges with recruiting and retaining emergency management and services volunteers in the face of demographic and societal changes.